2022
DOI: 10.4103/jfmpc.jfmpc_1164_22
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of magnesium supplement in patients with major depressive disorder under selective serotonin reuptake inhibitor treatment

Abstract: A BSTRACT Background: Major depression disorder (MDD) is a mental disorder that affects millions of people worldwide. This disease has negative impacts on quality of life and psychological-related functions. This is a multifactorial disorder; both genetic background and environmental factors have their role. Antidepressants are prescribed as the first line of treatment for patients with depressive disorders. Selective serotonin reuptake inhibitor (SSRI) antidepressants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Finally, seven eligible RCTs were included in the current systematic review and meta-analysis. Depression symptoms were assessed using Beck’s Depression Inventory (BDI) ( 5 , 10 ), BDI II ( 14 , 15 ), and the Hamilton Depression Rating Scale (HAM-D) ( 11 , 16 ) among the included studies. Moreover, one study reported a mean depression symptom score ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, seven eligible RCTs were included in the current systematic review and meta-analysis. Depression symptoms were assessed using Beck’s Depression Inventory (BDI) ( 5 , 10 ), BDI II ( 14 , 15 ), and the Hamilton Depression Rating Scale (HAM-D) ( 11 , 16 ) among the included studies. Moreover, one study reported a mean depression symptom score ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the seven included RCTs are summarized in Table 1 . These RCTs were published between 2016 and 2022 and were from the United States ( 16 ), Poland ( 11 ), and Iran ( 5 , 10 , 14 , 15 , 17 ). Two studies were exclusively performed on female subjects ( 14 , 17 ), and the other five were performed on both genders.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations